2017
DOI: 10.1007/s13300-017-0253-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Patients with Diabetes Who Exhibit Upper-Quartile Insulin Antibody Responses After Treatment with LY2963016 or Lantus® Insulin Glargine

Abstract: IntroductionWe compared insulin antibody response (IAR) profiles in patients with type 1 diabetes (T1D) or type 2 diabetes (T2D) who received LY2963016 insulin glargine (LY IGlar) or Lantus® insulin glargine (IGlar) and evaluated the potential relationship between higher IARs and clinical and safety outcomes with a focus on patients who exhibited antibody responses in the upper quartile.MethodsData from ELEMENT-1 (52-week open-label in T1D) and ELEMENT-2 (24-week, double-blind study in T2D) were analyzed. Maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Immunogenicity profiles appeared to be comparable across study groups in all studies. In two separate follow up analyses, Illag et al also supported the assessment that immunogenicity profiles were similar between LY2963016 and the respective reference product [ 44 , 45 ]. An investigation by Home et al demonstrated similar immunogenicity profile between SAR342434 and its reference product [ 46 ].…”
Section: Resultsmentioning
confidence: 87%
“…Immunogenicity profiles appeared to be comparable across study groups in all studies. In two separate follow up analyses, Illag et al also supported the assessment that immunogenicity profiles were similar between LY2963016 and the respective reference product [ 44 , 45 ]. An investigation by Home et al demonstrated similar immunogenicity profile between SAR342434 and its reference product [ 46 ].…”
Section: Resultsmentioning
confidence: 87%
“…In an immunogenicity analysis across ELEMENT-1 and ELEMENT-2 studies, data from evaluable patients showed no significant differences between GLY and its reference product with regard to insulin antibody levels or relationship to efficacy or safety outcomes including adverse events of special interest such as allergic reactions (comparable to hypersensitivity reactions) 19 . Similarly, a post hoc analysis of ELEMENT-2 that stratified patients by age evaluated insulin antibody levels and showed no difference between GLY and its reference product overall or by age group 20 .…”
Section: Hypersensitivity Reactionsmentioning
confidence: 98%
“…Studies that have evaluated biosimilar insulins against reference insulin products are very limited [10]. Lilly insulin glargine (LY IGlar; Basaglar ® , Eli Lilly and Company, Indianapolis, IN, USA, and Boehringer Ingelheim, Ingelheim am Rhein, Germany) is the first biosimilar insulin to have received approval in the highly regulated markets; it was approved in the EU and Japan in the year 2014 followed by approval as the first follow-on insulin in the USA [11]. It has recently received approval from the regulatory authorities in Korea, Taiwan, and India.…”
Section: Introductionmentioning
confidence: 99%